A frameshift-generated cancer neoepitope that controls tumor burden in prophylaxis as well as therapy - George, Mariam; Brennick, Cory; Hagymasi, Adam; Shcheglova, Tatiana; Al Seesi, Sahar; Rosales, Tatiana; Baker, Brian; Măndoiu, Ion; Srivastava, Pramod (The Journal of Immunology, 2025)
Insertion or deletion of one or two base pairs within a coding region causes a frameshift, which has the potential to generate neoepitopes (InDel-generated neoepitopes) that lack a self-counterpart and are entirely novel. Despite the obvious appeal of InDel-generated neoepitopes, and the demonstration of such candidate neoepitopes that can elicit a CD8 T-cell response, no InDel-generated neoepitopes that actually control tumors in vivo have been reported thus far. Here, in a mouse colon carcinoma line, we identify 11 InDels, only one of which generates a neoepitope that elicits tumor control in vivo in models of prophylaxis as well as therapy. Although this neoepitope has no self-counterpart, it has a low affinity (IC50 33,937.60 nM) for its MHC I allele. Despite its low affinity for MHC I, this neoepitope elicits antitumor activity in vivo through CD8 T cells. Furthermore, CD8 T cells elicited by this InDel-generated neoepitope, like the neoepitopes created by point mutations, show notably less exhaustion than classical immunogenic epitopes. Ironically, this InDel-generated neoepitope follows the same rules as noted for most of the tumor control-mediating neoepitopes generated by point mutations that have a poor affinity for MHC I alleles.
Keywords: Biology; Cancer research; Frameshift mutation; Gene; Genetics; INDEL Mutation; Immunology; In vivo; Indel; Mutation; dept.csc